POLA PEMBELAJARAN AKUNTANSI SEKOLAH MENENGAH KEJURUAN DENGAN MENGADOPSI TEACHING FACTORY - Wafrotur Rohmah; Suyatmini Suyatmini; Ummi Uswatun Hasanah; Bella Elysa Setiyana (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2021)
This study analyzes how the concept of teaching factory for accounting students in SMK. The objectives of this study: 1) Create a teaching factory conceptual model for accounting vocational students. 2) Establish a professional identity accountant concept for accounting vocational students. This type of qualitative research. The research design used ethnography. Data collection techniques using interviews and literature documentation. The validity of the data used is source triangulation. Data analysis techniques were carried out by means of data reduction, data presentation (including coding), and drawing conclusions. The results of the study show that: 1) The Prakerin implementation at SMK Negeri 4 Klaten has the aim of providing students to enter the world of work after graduation, by providing education and vocational training, 2) Sharia Banks or KJKS aims to support learning Sharia Banks in the accounting department specifically study sharia banking transactions where transactions are carried out in accordance with sharia principles, 3) students who practice at Mataram Bank learn firsthand how to process transactions in the bank, recording of these transactions to the recording of the financial statements.